2014
DOI: 10.1016/j.joi.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the assembly of interdisciplinary teams and its impact on performance

Abstract: Interdisciplinary teams are assembled in scientific research and are aimed at solving complex problems. Given their increasing importance, it is not surprising that considerable attention has been focused on processes of collaboration in interdisciplinary teams. Despite such efforts, we know less about the factors affecting the assembly of such teams in the first place. In this paper, we investigate the structure and the success of interdisciplinary scientific research teams. We examine the assembly factors us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 74 publications
(89 reference statements)
0
66
0
Order By: Relevance
“…This reflects researchers’ motivation to reduce uncertainty in the collaboration. Prior research has demonstrated that researchers are more likely to submit grant proposals with those with whom they have previously worked and that these proposals are more likely to be funded[46]. The second (reported by 48%) and third (37%) most important priorities were for researchers to seek collaborators who are recognized as successful researchers and good collaborators.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects researchers’ motivation to reduce uncertainty in the collaboration. Prior research has demonstrated that researchers are more likely to submit grant proposals with those with whom they have previously worked and that these proposals are more likely to be funded[46]. The second (reported by 48%) and third (37%) most important priorities were for researchers to seek collaborators who are recognized as successful researchers and good collaborators.…”
Section: Discussionmentioning
confidence: 99%
“…This reinforces our understanding that assembling teams with diverse cognitive resources is more likely to yield innovation. While researchers rarely team up with individuals who possess different knowledge sets, in other research we discovered that when this does occur, such teams are more likely to accomplish innovative outcomes, in this case the funding of a research proposal (Lungeanu et al, 2014). Unfortunately, we are unable to replicate those findings here because we do not have access to collaborations that did not result in publications.…”
Section: Discussionmentioning
confidence: 94%
“…Taken together with net findings about cognitive dissimilarity, this study suggests that innovation in networked research is most likely when teams draw upon individuals with diverse knowledge resources, but who also have prior collaborations with each other or with common others. The key to sustaining innovation in such teams is to reduce the possibility that close collaboration results in a reduction of the diversity in their knowledge expertise (Lungeanu et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the research by Lungeanu, Huang, and Contractor () also illustrates how the structural and relational (i.e. prior collaboration and citation relationships) properties of familiarity influence the collaborative process relative to the self‐organization of interdisciplinary team formation, for NSF grant proposals.…”
Section: The Mechanisms Of Team Formationmentioning
confidence: 96%